Aktualisasi Program Tahfidzul Qur’an Pada Sekolah Luar Biasa - Rizka Harfiani (Yayasan Rahmat Islamiyah, 2021)
The lack of special schools based on Islam and the Qur'an is one of the factors causing children with special needs to not get access to Islamic religious education. This study aims to analyze the actualization of the Tahfidzul Qur'an program at the integrated Islamic special school